2021
DOI: 10.1038/s41423-020-00619-y
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 nsp12 attenuates type I interferon production by inhibiting IRF3 nuclear translocation

Abstract: SARS-CoV-2 is the pathogenic agent of COVID-19, which has evolved into a global pandemic. Compared with some other respiratory RNA viruses, SARS-CoV-2 is a poor inducer of type I interferon (IFN). Here, we report that SARS-CoV-2 nsp12, the viral RNA-dependent RNA polymerase (RdRp), suppresses host antiviral responses. SARS-CoV-2 nsp12 attenuated Sendai virus (SeV)- or poly(I:C)-induced IFN-β promoter activation in a dose-dependent manner. It also inhibited IFN promoter activation triggered by RIG-I, MDA5, MAVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 42 publications
0
107
1
2
Order By: Relevance
“…Also, Nsp12, Nsp14, ORF3 and M proteins produced more than 50% inhibition of IFN-I induction after RIG-I overexpression [ 20 ]. However, subsequent studies generated contradictory results about the inhibitory activity of Nsp12 against IFN production and signaling [ 24 , 25 ], indicating that luciferase-based assays may be misleading [ 24 ]. The M protein was shown to impair IFN-I promoter activation by interfering with the prion-like aggregation of MAVS and its association with SNX8, thus disrupting the recruitment of the downstream components TRAF3, TBK-1 and IRF3 to the MAVS complex [ 26 ].…”
Section: In Vitro Inhibition Of the Ifn-i System By Sars-cov-2mentioning
confidence: 99%
“…Also, Nsp12, Nsp14, ORF3 and M proteins produced more than 50% inhibition of IFN-I induction after RIG-I overexpression [ 20 ]. However, subsequent studies generated contradictory results about the inhibitory activity of Nsp12 against IFN production and signaling [ 24 , 25 ], indicating that luciferase-based assays may be misleading [ 24 ]. The M protein was shown to impair IFN-I promoter activation by interfering with the prion-like aggregation of MAVS and its association with SNX8, thus disrupting the recruitment of the downstream components TRAF3, TBK-1 and IRF3 to the MAVS complex [ 26 ].…”
Section: In Vitro Inhibition Of the Ifn-i System By Sars-cov-2mentioning
confidence: 99%
“…8 – 10 It is reported that the recruitment of Th17 cells and increased IL-17 caused cytokine storm, and type I IFN response exacerbated inflammation in severe COVID-19 cases. 11 13 However, the underlying mechanism of cytokine storm in COVID-19 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the IFN-I/λ response is now thought to be a critical host response against SARS- CoV-2 infection and its pathogenesis (Grajales-Reyes and Colonna, 2020; Hadjadj et al, 2020; Kim and Shin, 2021; Sa Ribero et al, 2020; Saichi et al, 2021; Trouillet-Assant et al, 2020) . Recent studies have shown that SARS-CoV-2 can evade from this initial control by the IFN-I/λ response via manifold inhibitory mechanisms interfering with both the sensing and the signaling pathways within infected cells (reviewed in (Kim and Shin, 2021; Min et al, 2021; Park and Iwasaki, 2020; Sa Ribero et al, 2020) ), and e.g., illustrated in (Kimura et al, 2021; Lei et al, 2020; Miorin et al, 2020; Saichi et al, 2021 ; Wang et al, 2021; Xia et al, 2020) ). This immune evasion might lead to an increased viral load, followed by widespread inflammations (Sa Ribero et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%